Inflammatory fibrous hyperplasia due to maladapted prosthesis: Therapeutic considerations and case report (Research, Society and Development, 2021)
Inflammatory fibrous hyperplasia (IFH) known as Fissured Epulis is considered a frequent proliferative lesion in the oral cavity, it is usually asymptomatic, resulting from a hyperplastic reaction of the connective tissue. Its treatment of choice is surgical excision, which can be performed with a cold scalpel (conventional), laser surgery, electrosurgery and cryotherapy. The methodology used was an active search in an electronic database in Pubmed/Medline, Scielo, Portal Periódicos CAPES and LILACS in scientific articles published in the last 10 years in English and Portuguese, using the descriptors: Hyperplasia, Denture, Complete, Pathology , Oral, Surgery, Oral. After the eligibility criteria, the articles were selected and the clinical case reported for discussion of diagnostic and treatment approaches. The aim of this paper is to report a clinical case of IFH as well as to make a brief comparison of the treatment methods that can be used in the treatment of IFH. Case Report: Female patient, 73 years old, with chief complaint of tissue growth in the gingival region and discomfort in the use of total denture, was treated satisfactorily by electrosurgery. Conclusion: Electrosurgery is the most accessible and effective method in the surgical treatment of Fissured Epulis.